Treatment of 2-diazo-4, 6-dinitrophenol (DDNP) wastewater using TiO2/SiO2 composite film in new photocatalytic reactor - Shen, Rongyan; Liu, Fang; Li, Te; Xu, Xia; Liang, Yuting; Zhao, Xingqing; Zhang, Wenyi (Chemical Industry and Chemical Engineering Quarterly, 2015)
TiO2/SiO2 composite film was used to modify the surface of the filter media sintered by coal refuse. 2-Diazo-4,6-dinitrophenol (DDNP) wastewater was used as the response substrate to test its photocatalytic activity in new self-made photocatalytic reactor. The particle morphology and physico-chemical properties of the modified filter media were characterized by the scanning electron microscope (SEM), energy dispersive spectrometer (EDS), and X-ray diffraction (XRD). The influencing factors of the photocatalytic activity of the modified filter media were studied. When the modified filter media was used, the decolorization rate and COD removal rate of DDNP wastewater reached 70.00% and 60.85%, respectively. But unmodified filter media almost had no photocatalytic activity. The orthogonal experiment showed that the optimal working parameters separately were: 59:1 of Ti/Si in the TiO2/SiO2 composite film, pH 1, 7 ml L-1 H2O2, and 3000 times chroma (equivalent initial concentration of DDNP wastewater). Under the above condition, the decolorization rate and COD removal rate separately reached 98.50% and 92.50% for 1 h photocatalytic reaction. Under the condition of illumination and aeration, the photocatalytic activities were obviously higher than those under only illumination or aeration. nema